Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja pada Pegawai Perusahaan Daerah Air Minum Tirtanadi Cabang Sunggal - Putranto, Muhammad Agung; Hasibuan, Hasrul Azwar; Robain, Wilchan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the effect of motivation and work environment on employee performance at the Regional Drinking Water Company (PDAM) Tirtanadi Sunggal Branch. The approach used is quantitative. Data was collected through the distribution of questionnaires to 52 respondents who are employees of PDAM Tirtanadi Sunggal Branch. The questionnaire was constructed based on the indicators of each variable, using a Likert scale to measure the respondents' responses. The data analysis technique used is multiple linear regression with the help of SPSS version 25. The analysis results show that the motivation variable has a positive and significant effect on employee performance, with a t value of 3.587 > t table 2.00 and a significance of 0.001 < 0.05. Work environment variables also have a positive and significant effect, with a calculated t-value of 6.160 > table t 2.00 and a significance of 0.000 < 0.05. Simultaneously, motivation and work environment significantly influence employee performance, as shown by a calculated F-value of 42.15 > table F 3.19 and a significance value of 0.000 < 0.05. Thus, it can be concluded that both motivation and work environment have a significant effect on the performance of employees at PDAM Tirtanadi Cabang Sunggal, both partially and simultaneously.